Penguatan Literasi Digital, Kesehatan, dan Lingkungan pada Masyarakat Kampung Mayak - Puteri Nabilla, Herssya; Maya Devi, Amelia; Muhammad Rafi, Ariz; Billal Ramadhani, Deani; Prayoga Putra, Helga; Hari Mardika, Isnan; Gusti Romadona, Karima; Nurhakim, Lukman; Ferdiansyah, Rio; Fitriana, Riri; Alfiana Azzahra, Viola (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
The community service program in Kampung Mayak, Mayak Village, Curugbitung Subdistrict, was implemented in response to the community's limited access to technology and suboptimal understanding of technology, health, and environmental management. This activity aims to increase the basic knowledge capacity of students and the community through the implementation of integrated socialization designed systematically. Community service partners included early childhood education centers, kindergartens, elementary schools, junior high schools, and the Mayak Village community. The implementation method used a participatory, interactive, and collaborative approach with the Participatory Action Research (PAR) method through health demonstrations, creative garden creation, basic computer training, tutoring, afternoon exercises, and village mutual assistance. Evaluation was conducted after direct observation, independent practice, and brief question and answer sessions to measure participants' understanding and behavioral changes. The results showed an increase in the fine motor skills of PAUD children, the habit of clean living among kindergarten and elementary school students, the strengthening of environmental literacy through the recycling of used bottles, and an increase in digital literacy among junior high school students. Collaborative activities also strengthened social interaction and community awareness of health and environmental hygiene. Overall, the integrated socialization model was effective in integrating technology, health, and environmental aspects. These findings are significant because they present realistic, applicable, and potentially sustainable empowerment practices for schools and the Mayak Village community.